Effects of pore structure characteristics on performance of sintered bi-porous Ti3AlC2 wicks - Yingwen Cao; Chunsheng Guo; Dongting Wu; Yong Zou (Materials Research Express, 2021)
Loop heat pipe, carried out by liquid-gas phase transition, has been attracted as an efficient heat management device in high-heat-flux, long-distance and anti-gravity situations. The capillary pressure provided by the porous wick in the evaporator drives circulation for working liquid, affecting the heat exchange efficiency for loop heat pipes directly. In this work, the bi-porous Ti _3 AlC _2 wick was produced by reaction sintering and pore formers dissolution and porosity and pore size were regulated by varying pore formers content and cold pressure. The pore size distribution was characterized by mercury intrusion and effects on capillary performance and thermal conductivity were also analyzed. The porosity and proportion of large pores increased with the increased pore formers content, causing the enhancement of capillary performance and the reduction of thermal conductivity. As the cold pressure increased, pore size distribution concentrated, the proportion of fine pores increased and the porosity fluctuated slightly, increasing the capillary pressure and improving capillary performance and thermal conductivity. Based on experimental results, the parameter of pore size proportion was proposed to modify the Alexander model to predict the thermal conductivity of porous materials accurately, guide the design for pore structure and promote the transfer capacity.